2021
DOI: 10.3390/antiox10010126
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaced Actions of Curcumin in Pregnancy Outcome

Abstract: Curcumin, also known as diferuloylmethane, is the main polyphenolic substance present in the rhizomes of Curcuma longa L. This plant showed many beneficial effects and has been used since ancient times for both food and pharmaceutical purposes. Due to its pleiotropic functions, curcumin consumption in the human diet has become very common thanks also to the fact that this natural compound is considered quite safe as it does not have serious side effects. Its functions as an anti-inflammatory, anti-oxidant, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 159 publications
0
45
0
Order By: Relevance
“…There are animal model studies on the use of curcumin in pregnancy. Due to the anti-inflammatory activity of this compound, the possibility of using this compound in the treatment of complications of pregnancy has been suggested, including Gestational Diabetes Mellitus, PreTerm Birth, Preeclampsia and exposure to toxic agents and pathogens [ 21 ].…”
Section: Medicinal Activities Bioavailability and Metabolism Of Curcu...mentioning
confidence: 99%
“…There are animal model studies on the use of curcumin in pregnancy. Due to the anti-inflammatory activity of this compound, the possibility of using this compound in the treatment of complications of pregnancy has been suggested, including Gestational Diabetes Mellitus, PreTerm Birth, Preeclampsia and exposure to toxic agents and pathogens [ 21 ].…”
Section: Medicinal Activities Bioavailability and Metabolism Of Curcu...mentioning
confidence: 99%
“…Moreover, endovenous use of curcumin is safe if used if the dose administered is lower than that used orally. In pregnant animals, curcumin showed to be safe, but further studies are needed to confirm its safety in pregnant women (79,80). Curcumin is also a nontoxic, non-mutagenic, non-carcinogenic, non-photo toxic agent and considered safe at lower doses than oral doses in intravenous administration in humans.…”
Section: Curcuma Longamentioning
confidence: 99%
“…Similarly, animal studies also indicated that rosiglitazone mitigated the decrease of placental diameter and fetal weight caused by TCS. In addition, curcumin, a natural compound and a modulator of PPARγ, has been known to have beneficial effects on pregnancy outcomes [ 53 , 54 ]. It will be interesting to know the effect of curcumin or other natural PPARγ modulators on TCS placental exposure in the future.…”
Section: Discussionmentioning
confidence: 99%